(untitled) (Pedagogical Horizons, 2025)
This submission examines the curricular relevance of remembrance culture and democracy education in Austrian history curricula for lower secondary education. The main focus is on analysing the development of terminology and the embedding of concepts related to remembrance culture and democracy education in terms of content over time. The starting point is the premise that memory culture can be understood as a socially structured, group-specific and processual way of dealing with the past (Assmann, 2013). The study is theoretically grounded in central concepts of collective, communicative and cultural memory according to Halbwachs (1985) and Mathias Berek (2009). Using quantitative frequency analysis, the curriculum documents are examined for the use of relevant terms such as ‘memorial sites,’ ‘anti-Semitism,’ ‘Holocaust,’ or ‘democracy education.’ In frequency analysis, the occurrence of a criterion (e.g., a specific word or statement) in a document is counted and recorded in a table. The results show that in older curricula, aspects of remembrance culture are treated in a rudimentary manner at best (BMUKK, 2000), whereas in newer curricula they are treated explicitly and in an increasingly differentiated manner (BMBF, 2016; BMBWF, 2023). The focus is particularly on the topic of National Socialism and Holocaust education. The more recent curricula increasingly emphasise process-oriented, reflexive and multi-perspective approaches, which implies a stronger emphasis on memorial site education and deconstructive methods (Hellmuth & Kühberger, 2016). Overall, it should be made clear that remembrance culture and democracy education are not only understood as the generation of knowledge, but also as a didactic principle that contributes to the promotion of historical orientation, democratic education and a reflective awareness of history (Pandel, 2014). The curricular integration of concepts of remembrance culture thus proves to be central to critically reflective history teaching and the formation of a democratic historical consciousness in the Austrian school context.